Lectures on advanced mathematical methods for physicists - Mukhi, Sunil; Mukunda, N. (World Scientific, 2010)
This book presents a survey of Topology and Differential Geometry and also, Lie Groups and Algebras, and their Representations. The first topic is indispensable to students of gravitation and related areas of modern physics (including string theory), while the second has applications in gauge theory and particle physics, integrable systems and nuclear physics.